Alcohol Sensing Properties of Sol-gel Derived TiO(2) Thin Film - (:unkn) unknown (AMER INST PHYSICS, 2009)
In this work, alcohol sensing properties of pure TiO(2) thin film were investigated. TiO(2) were deposited on glass substrate patterned with interdigitated transducer (IDT) by a sol-gel dipping method. Precursor solution is prepared by dissolving of titanium(IV) n-butoxide in methanol Then glacial acetic acid was added into the solution. Final heating was performed at 773 K in air. Crystal structure of the film was investigated using X-ray diffraction Target gases were vapors of ammonia, methanol, ethanol, and isopropyl alcohol. The measurements were performed in the temperature range of 293 K and 523 K Gas concentrations were kept in the range of 0.4%-18%. Response characteristics of the film were determined by means of change in dc conductivity as a function of gas concentration and temperature During the measurements 1 volt was applied to the IDT. Gas concentrations were controlled by mass flow controller. The film showed good sensitivity to the target gases in the measurement range The results showed that responses of the film were reversible and depend on the operating temperature and gas concentration.
Keywords: Titanium dioxide; sol-gel; sensor; VOC; thin film